Adverse childhood experiences in families with multiple members diagnosed to have psychiatric illnesses. (November 2020) - Someshwar, Amala; Holla, Bharath; Pansari Agarwal, Preeti; Thomas, Anza; Jose, Anand; Joseph, Boban; Raju, Birudu; Karle, Hariprasad; Muthukumaran, M; Kodancha, Prabhath G; Kumar, Pramod; Reddy, Preethi V; et al.
Objective: Adverse childhood experiences are linked to the development of a number of psychiatric illnesses in adulthood. Our study examined the pattern of adverse childhood experiences and their relation to the age of onset of major psychiatric conditions in individuals from families that had ⩾2 first-degree relatives with major psychiatric conditions (multiplex families), identified as part of an ongoing longitudinal study. Methods: Our sample consisted of 509 individuals from 215 families. Of these, 268 were affected, i.e., diagnosed with bipolar disorder ( n = 61), obsessive–compulsive disorder ( n = 58), schizophrenia ( n = 52), substance dependence ( n = 59) or co-occurring diagnoses ( n = 38), while 241 were at-risk first-degree relatives who were either unaffected ( n = 210) or had other depressive or anxiety disorders ( n = 31). All individuals were evaluated using the Adverse Childhood Experiences – International Questionnaire and total adverse childhood experiences exposure and severity scores were calculated. Results: It was seen that affected males, as a group, had the greatest adverse childhood experiences exposure and severity scores in our sample. A Cox mixed effects model fit by gender revealed that a higher total adverse childhood experiences severity score was associated with significantly increased risk for an earlier age of onset of psychiatric diagnoses in males. A similar model that evaluated the interaction of diagnosis revealed an earlier age of onset in obsessive–compulsive disorder and substance dependence, but not in schizophrenia and bipolar disorder. Conclusion: Our study indicates that adverse childhood experiences were associated with an earlier onset of major psychiatric conditions in men and individuals diagnosed with obsessive–compulsive disorder and substance dependence. Ongoing longitudinal assessments in first-degree relatives from these families are expected to identify mechanisms underlying this relationship.